Faktor yang Memengaruhi Kehamilan Sebelum Menikah Pada Remaja Di Empat Puskesmas Kabupaten Sikka Tahun 2017 - Agnes Krisylva; Hermanto Tri Joewono; Margarita M Maramis (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Pre-marital pregnancy in adolescents contains very complicated and complex issues, especially for those who are directly involved in it. Pre marital pregnancy in adolescents in Sikka District in 2017 was 191 people (47%) of the total number of teenagers who were pregnant. Many factors influence pregnancy before marriage in adolescents including age, order of children, education, parents job, family income, parental marital status, parenting, culture and religiosity.The purpose of this study was to analyze the factors that influence the occurrence of pregnancy before marriage in adolescents in four Community Health Centers of Sikka District . Methods: An analytic observational study with a case control study design. The sampling technique used is Quota Sampling. Sampling in four Community Health Centers with a high percentage of pregnancy before marriage. The control group was taken with the same age match, namely age 10-19 years in the same area, each of 90 teenagers were pregnant before marriage (case) and teenagers were pregnant after marriage (control).Result: The multiple logistic regression test showed that together there was a significant relationship between parenting of the parents (p <0.05, OR = 14.107), parental marital status (p <0.05, OR = 4.359) and religiosity (p <0.05 , OR = 2,651) with pre-marital pregnancy in adolescents. Age, order of children, education, parental work, parents job, income and culture are not related to pre-marital pregnancy in adolescents in four Community Health Centers of Sikka District.Conclusion: Bad parenting factors play the most important role in the occurrence of pregnancy before marriage in adolescents in four Community Health Centers of in addition to the factors of parental marital status and religiosity.